The Influence of a Heuristic Approach with Blended Learning on Students' Critical Thinking Abilities - Delia Oktaviana; Uus Kusdinar (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2023)
The students lack of habit in critical thinking is the background in this research. Lack of abilities due to the use of conventional learning models, so that learning activities are passive. The purpose of this study was to determine whether heuristic learning with blended learning method had an effect on the critical thinking skills of eight grade students of SMPN 12 Yogyakarta. This research is a type of quasi experimental. The population in this study were student of class VIII SMPN 12 Yogyakarta. Where class VIII D is the control class and VIII E class is the experimental class. The object of this research is the use of a heuristic approach with the help of the blended learning method. Data collection was carried out using test techniques. The instrument use in collecting data about students critical thinking skills. The test instrument used is the content validity test. Data processing is done by using descriptive analysis and inferential analysis. Based on the research that has been done, this study shows that the use of a heuristic learning approach with the help of eighth grade students if SMP N 12 Yogyakarta. The result of this study can see from the result of tcount = 2.142 and ttable = 1.99 which means that tcount > ttable so it can be said if there is an effect of using a heuristic approach with the help of the blended learning method on student’s critical thinking skills.